Behavior of coated forming tools with TiAlN coatings grown by Triode Magnetron Sputtering (2015)
This research focusses on tribological analysis of Titanium Aluminum Nitride (TiAlN) coatings deposited by means of Triode Magnetron Sputtering, when used as a protective coating on forming tools. The analysis is carried out from the microstructural properties which directly influence the tribological behavior. It was observed that the predominant wear mechanisms on the surface are delamination and tribo-oxidation; an increase in the useful life of the tool was observed making hard coatings an excellent alternative in the metalworking industry.